PENGEMBANGAN MEDIA POLIOMINO PADA PEMBELAJARAN JARING-JARING KUBUS DAN BALOK MELALUI PROJECT BASED LEARNING DI SD - Yulia Marni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
Mathematics is a subject that is often considered difficult, but this field of study is always present at every level of education, from elementary school to university. In general, mathematics material is related to one another, so that when students do not understand concepts at the basic level, it will affect the following levels. Ignorance of this material makes mathematics unattractive and avoided by students, even though this material has many benefits in everyday life. The purpose of writing this research is to develop the use of polyomino media and see its benefits in increasing students' understanding of the material for nets of cubes and blocks by using the project based learning (PBL) learning model in elementary schools (SD). The material for nets for cubes and blocks is difficult material, because of the 11 patterns for nets for cubes and 54 patterns for existing blocks, students often only know about 2 or 3 examples of existing patterns. This research was conducted at SD Negeri 06 Lasi Mudo Agam with a total of 30 students. The method that the writer uses is observation and interviews which are analyzed descriptively. The results of the research show that Poliomino media can develop students' creativity in finding many patterns of nets of cubes and blocks and can improve the ability to solve problems in mathematics.